Depression in the elderly as a significant clinical problem - Eliza Niewiadomska; Jakub Husejko; Marcin Kujaciński; Aleksandra Wijata; Marcin Falkowski; Kornelia Kędziora-Kornatowska (Kazimierz Wielki University, 2019)
Introduction: Depression is a very common mental disorder among older people. It limits life activity and interests. It causes difficulties in making decisions or actions. It introduces somatic and emotional changes, which in older people becomes a problem on a large scale. Diagnosis of depressive disorders has very high clinical value.Depression is often associated with chronic diseases that often accompany the elderly. Material and Methods: The paper reviews literature using the EBSCO and Google Scholar databases. Articles have been analyzed using the keywords depression, depression of the elderly, care for the elderly, treatment of depression, diagnosis of depression, clinical symptoms. The article presents depression as a problem among older people, its symptoms, treatment and care for such people. Results: Treatment of depressive disorders is based on pharmacology and psychotherapy. Care and the presence of loved ones are very important. Commitment to physical activity improves emotional balance. Conclusions: Depression in older people creates a problem in terms of diagnosis and clinical aspect. Depression reduces the quality of life, which means that older people cannot perform basic life activities on their own. Reduces motivation and interest in the environment. Correct diagnosis enables quick implementation of treatment that will allow you to recover. Key words: depression, treatment, care, old age, diagnosis, epidemiology, SSRI, NSRI, helpline